2013
DOI: 10.1007/s00068-013-0321-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between acute appendicitis and appendiceal mucocele: is this possible preoperatively?

Abstract: A threshold 10-mm diameter of the appendix under compression is a useful preoperative measurement for differentiating between appendiceal mucocele and acute appendicitis. Microhematuria is simple test that can provide a significant role in supporting the clinical diagnosis of appendiceal mucocele in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
7
2
Order By: Relevance
“…Although it is reported that half of the patients are asymptomatic [12,13], our study reveals that clinical features on presentation included abdominal pain, abdominal distention, abdominal mass and hematochezia. A number of Appendiceal mucocele patients were misdiagnosed as acute appendicitis [14,15]. However, only 3 of 51 patients in our study was found to have tenderness and rebound pain typical of acute appendicitis.…”
Section: Discussioncontrasting
confidence: 57%
“…Although it is reported that half of the patients are asymptomatic [12,13], our study reveals that clinical features on presentation included abdominal pain, abdominal distention, abdominal mass and hematochezia. A number of Appendiceal mucocele patients were misdiagnosed as acute appendicitis [14,15]. However, only 3 of 51 patients in our study was found to have tenderness and rebound pain typical of acute appendicitis.…”
Section: Discussioncontrasting
confidence: 57%
“…On this basis, the authors assigned a point to each of these factors (large appendiceal diameter, low WBC count and presence of microscopic haematuria) resulting in a predictive score and a stratification of patients into three groups (Score I: 0 points; Score II: 1 points; Score III: ≥2 points). The scoring system for patients with ≥2 points was proven to have an area under the curve (AUC) of 0.855 using a receiver-operating characteristic curve with a sensitivity of 73.33% and a specificity of 89.87% 6. Of note, the patient we presented had an appendiceal diameter of 40×60 mm (by CT scan), a WBC count of 9900/mm 3 and a preoperative urine sample documenting 4 erythrocytes/µL.…”
Section: Discussionmentioning
confidence: 89%
“…These findings suggest that treatment delays are predominantly influenced by factors within the healthcare system that can be further mitigated with improved professional education and streamlining of administrative processes. Considering the well-documented challenges involved in evaluation of peritoneal malignancies given their significant heterogeneity, varying nature of initial presentation and overall rare occurrence ( 14 , 15 , 17 , 31 34 ), healthcare professionals at large would benefit from better awareness on the initial presentations, appropriate evaluation strategies and treatment options for peritoneal malignancies. Additionally, treatment delays incurred here are also contributed at least in part by patients’ failure to recognize symptoms that suggest underlying peritoneal malignancies which resulted in delayed presentation to primary care.…”
Section: Discussionmentioning
confidence: 99%